Fragrances in Remote Areas - Vecchiato, Marco (Springer Science and Business Media Deutschland GmbH, 2024)
Far from the general idea of pristine environments, remote areas may be affected by emissions from local human settlements and by the long-range transport of pollutants. Fragrances, as widely used components in household and personal care products (PCPs), may derive from both these types of sources. Consequently, the presence of nitro, polycyclic, and macrocyclic musks, as well as of other non-musk fragrances, mainly salicylates, was found in remote environments, including the Arctic, Antarctica, and high-altitude mountains. Several studies reported the distribution of fragrances in different environmental matrices, such as air, snow, water, biota, and sediment, also reflecting the reactivity of these contaminants during transport. The temporal trends of the environmental concentrations of fragrances in remote areas depend on the market volumes of these substances and are influenced by melting dynamics, as also demonstrated by sediment and ice core archives. However, major knowledge gaps need to be addressed to understand the impact of fragrance contaminants in polar and remote ecosystems.